2023
DOI: 10.7759/cureus.36464
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Symptomatic Venous Thromboembolism (VTE) in 8,885 Elective Total Hip Arthroplasty Patients Receiving Post-operative Aspirin VTE Prophylaxis

Abstract: Background: Venous thromboembolism (VTE) is a potentially reducible cause of morbidity and mortality in patients undergoing elective hip arthroplasty surgery. The balance of post-operative VTE prophylaxis and risk of post-operative haemorrhage remains at the forefront of surgeon's mind. The National Institute for Health and Care Excellence (NICE) published updated guidelines in 2018 which recommend the use of both mechanical and pharmacological methods in patients undergoing elective total hip arthroplasty (TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…[9,[30][31][32] Another meta-analysis reported no statistically significant differences between aspirin and enoxaparin for DVT and PE; overall evidence quality was low and validation is required from more RCTs. [33] Coveney [34] et al supported aspirin as effective in preventing symptomatic VTE after THA in 8885 patients receiving aspirin. However, we observed that LMWH anticoagulation during hospitalization and continued oral aspirin for 6 weeks after discharge was significantly intrusive.…”
Section: Discussionmentioning
confidence: 99%
“…[9,[30][31][32] Another meta-analysis reported no statistically significant differences between aspirin and enoxaparin for DVT and PE; overall evidence quality was low and validation is required from more RCTs. [33] Coveney [34] et al supported aspirin as effective in preventing symptomatic VTE after THA in 8885 patients receiving aspirin. However, we observed that LMWH anticoagulation during hospitalization and continued oral aspirin for 6 weeks after discharge was significantly intrusive.…”
Section: Discussionmentioning
confidence: 99%
“…The average molecular weight of sodium sulfated heparin is below 8000 Da, and at least 60% of its molecular weight is distributed below 8000 Da. 20 , 21 The average molecular weight of sulfadoxine sodium is below 8000 Da and at least 60% of the molecular weight is below 8000 Da. Because of its small molecular weight and monotonous action, sulfadoxine does not have many of the important pharmacological properties of pharmaceutical heparin, except for its specific binding to the anti-Xa factor.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that platelets contribute to the initiation and progression of venous thromboembolism and indicate that aspirin is not only able to prevent arterial thrombosis, but also moderately reduces venous thromboembolism [ 88 , 89 ]. More recent studies and meta-analyses support this assumption [ 90 , 91 , 92 ], with the caveat that non-vitamin K antagonist oral anticoagulants also play a crucial role in this setting [ 93 ]. Nevertheless, a drug with a dual preventive action on venous and arterial thrombosis would be welcome in patients with an increased risk for both (e.g., infectious disease patients with an increased risk of disseminated intravascular coagulation or infection-induced coagulopathy) [ 14 ].…”
Section: Aspirin As An Antiplatelet/antithrombotic Agentmentioning
confidence: 99%